Food Disgust in Narratives of Migrant Voices in Italy. The Rejection of Food as a Form of Identity Renegotiation and Resistance - Baldaro, Michele (I.S. MED. - Interdisciplinary Studies on the Mediterranean, 2025)
Following a literary perspective, this paper explores the role of dietary choices in the identity restructuring process of individuals, particularly within the works of migrant writers. According to Vito Teti (2001) and Horn (2010), food serves as a form of cultural defense and community cohesion for immigrants. Additionally, Lorena Carrara (2013) notes that food disgust plays a role in shaping both individual identity and a sense of belonging for social groups. Building upon these premises, the article analyzes the role of disgust within selected texts by migrant and second-generation authors in their process of assimilation, hybridization, or resistance in Italy. Specifically, the research focuses on stories that emphasize the significance of food and rejection of food as indicators of cultural belonging, such as those from the anthologies Matriciana/Cous cous (2002), Pecore nere (2005), Mondopentola (2007), and Amori bicolori (2008), as well as Lakhous’s novel Scontro di civiltà per un ascensore a Piazza Vittorio (2006). In these literary works, food disgust becomes a valuable key for literary interpretation. Indeed, Montanari argues that different cultures encounter each other primarily through food (2002). Moreover, at the base of dietary disgust there are the omnivore’s paradox and the principle of incorporation (Fischler 1980, Nicolosi 2007, Megli 2017). Thus, the rejection of the Other’s food or, conversely, the rejection of one’s own community’s food highlight the diverse outcomes of integration dynamics in the new socio-cultural context for migrants. The potential outcomes of the renegotiation of the migrant’s identity, as presented in the case studies, range from the risk of self-annihilation to the resistance against the Otherness of the new host society. In conclusion, by establishing a link between narrative, food sociology, and the analysis of the migration process in Italy, this paper demonstrates how disgust provides a new lens for interpreting the identity restructuring experience in migrant and second-generation writers.